Pendampingan Pembuatan Nomor Induk Usaha (NIB), PIRT, dan Sertifikat Halal Pada UMKM di Desa Ngrimbi, Kecamatan Bareng, Kabupaten Jombang - Daru Teja Sasangka; Budi Prabowo (Yayasan Daarul Huda Kruengmane, 2023)
Micro, Small, and Medium Enterprises (UMKM) are one of the pillars of the national economy. An UMKM is essential to have legal documentation for their business to protect them legally. This community service aims to provide assistance in obtaining legal documents such as the Business Identification Number (NIB), PIRT, and the Halal Certificate for the UMKM entrepreneurs in Ngrimbi Village, Bareng District, Jombang Regency. Generally, many of these entrepreneurs lack awareness of the importance of legal documentation for their businesses, leading to negative assumptions about the legitimacy of their businesses. The implementation process of this activity involves several stages. It begins with conducting surveys among the UMKM entrepreneurs in Ngrimbi Village to gather data on their numbers and potential. Next, there will be a socialization phase emphasizing the significance of legal documentation for UMKM, and the process continues with providing assistance in obtaining the necessary legal documents such as the Business Identification Number (NIB), PIRT, and the Halal Certificate.